In the PaLRaP Spotlight: Ann L. Kemper - Stephanie Campbell (Pennsylvania Libraries: Research & Practice, 2018)
Ann Kemper is Supervisory Librarian, United States Army Garrison Casey, Camp Red Cloud and Camp Hovey, South Korea.